PENGARUH SALES PROMOTION DAN KUALITAS PELAYANAN TERHADAP MINAT BELI ULANG YANG DIMEDIASI KEPUASAN KONSUMEN PADA DEALE YAMAHA SURYA INTI PUTRA ASEMBAGUS SITUBONDO - Waskitha, M. Ghariez Aji; Hamdun, Edy Kusnadi; Ediyanto, Ediyanto (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
The aim of the study is to determine the effect of sales promotion and service quality on repurchase intention mediated by consumer satisfaction at the AsembagusSitubondo Yamaha Surya Inti Putra Dealer. The sampling technique used in this study was simple random sampling with the Slovin formula with a tolerable error rate of 10% for 96 consumers. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM) The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Sales promotion has a positive and significant effect on consumer satisfaction, service quality has a positive and significant effect on consumer satisfaction, sales promotion has a positive and significant effect on repurchase intention, service quality has a positive and significant effect on repurchase intention, consumer satisfaction has a positive and significant effect on repurchase intention, sales promotion has a positive and significant effect on repurchase intention through consumer satisfaction, service quality has a positive and significant effect on repurchase intention through consumer satisfaction